A predictive model for reproductive performance following abortion in Thoroughbred mares. (12th January 2013) - Schulman, M. L.; Kass, P. H.; Becker, A.; Van der Merwe, B.
Abstract : Pregnancy losses include early embryonic death (EED) and later (postimplantation) abortion. Abortions, particularly Equid herpesvirus (EHV‐1) abortion epizootics, cause severe economic and production losses. The long‐term effects of EHV‐1 and other abortions on subsequent reproductive performance in broodmare populations, however, remain undefined. This study described the relationships of EED and abortion with the following reproductive outcomes in Thoroughbred systems: breeding efficiency, month of last breeding, subsequent pregnancy and live foal rates. A prospective cohort study in broodmare populations following EHV‐1 epizootics on two South African farms was used to develop predictive models of the relative influences and interactions of reproductive variables associated with EHV‐1 and other abortion causes on reproductive performance. EED predicted all the reproductive outcomes. Abortion predicted increased effort and month of breeding to establish pregnancy, but not becoming pregnant or foaling. Increasing age predicted decreased reproductive efficiency, and pregnancy and foaling probabilities. Mare reproductive status predicted breeding efficiency and the last month of breeding, but not establishing pregnancy. The last month of breeding predicted efficiency, pregnancy and foaling. Interestingly, breeding in the first month of the season was associated with an improved probability of pregnancy among barren mares.